Perception of secondary school counsellors on their leadership roles in the education of students with special needs in Lagos State, Nigeria (2017)
The knowledge of whether secondary school counsellors envision themselves as leaders in the educational setting and the extent to which this perspective has been transformed to functional leadership practices is unclear. However, educators recognize the unique position occupied by guidance counsellors and the essential roles they play especially, in the education of persons with special needs. This study therefore, examined secondary schools counsellors’ perceptions of their leadership roles in the education of persons with special needs. It also investigated if any difference exists in secondary school counsellors’ perceptions of their leadership roles and some selected variables of age, gender, experience, or school status. The study adopted descriptive research, design. The sample of the study comprised (40) (that is, thirty-four (34) females and six (6) males), professional secondary school counsellors, from 40 (that is, 30 public and 10 private) secondary schools who are also members of the Lagos State Chapter of the counselling Association of Nigeria (CASSON). The respondents were selected using a stratified random sampling technique and purposive sampling. All respondents have some knowledge of special education. The respondents were purposively selected from four education districts of Lagos State out of six. Four hypotheses were formulated, while a self-developed questionnaire on counsellors’ perception, of their leadership roles was the main instrument for data collection. The data collected were analyzed using t-test. The results of the study indicated that respondents see themselves as leaders in the education sector irrespective of counsellors’ age, gender, years of experience and school status (public or private). Based on the findings, recommendations were made which include that guidance counsellors should engage in functional leadership practices in order to positively impact achievement of all students especially those with special needs.